Of a Village Bomoh and the Lottery: content schemata influence on second language reading - Mohd Radzi, Amizura Hanadi; Abd Aziz, Noor Hashima (Australian International Academic Centre, Australia, 2013)
This paper discusses a study on the aspects of content schemata in second language reading, focusing on two contemporary short stories, i.e. "A Quid of Sirih, A Bowl of Water" and "The Lottery." The study explores the cognitive processes of one UiTM Perlis degree level student, reflecting on his L2 reading processes.The objective of the study was to explore the role of content schemata in relation to learners' comprehension by looking at how the learner processed content-familiar and unfamiliar texts. One of the data collection techniques used was think aloud protocol.The analysis of the transcriptions was guided by the list of mental actions by Brown (1980).Two in-depth interview sessions were conducted to triangulate the data collected.The interview transcripts were analyzed for recurring patterns and then classified into categories.The findings imply that content schemata contributes to learners' understanding of a text as content schemata facilitates comprehension.